Adverse reactions to four types of monovalent antivenom used in the treatment of snakebite envenoming in South China. (November 2022) - Li, Qianqin; Zeng, Liangbo; Deng, Haiyan; Liang, Qing
Abstract: To evaluate the adverse reactions associated with the four types of monovalent antivenom currently used in China, we retrospectively analysed the data of all patients admitted for snakebites who received antivenom treatment at the main institution for the treatment of venomous snakebites in Guangzhou from January 2013 to December 2021. A total of 1658 patients were analysed in our study, and 60.7% (n = 1007) of the snakebite patients received antivenom treatment. The incidence rate of adverse reactions that occurred after the administration of all types of monovalent antivenom was 4.9% (n = 49), and the incidence rate of acute adverse reactions was 2.7% (n = 27). The number of adverse reactions that occurred was 38/744 (5.1%) in patients who received prophylactic application of glucocorticoids alone and 10/217 (4.6%) in those who received a combination of antihistamines and glucocorticoids ( P  = 0.83). The average doses of the antivenoms used in patients exhibiting acute adverse reactions and serum sickness were 3.31 ± 0.75 vials and 2.36 ± 0.26 vials, respectively ( P  = 0.28). The antivenom skin test showed high specificity (98.3%, 95% CI: 97.24%–99.01%) but low sensitivity (14.3%, 95% CI: 6.41%–27.86%). Our results showed that the four types of monovalent antivenom were safe. No significant difference was observed between the use of glucocorticoids alone and the use of antihistamines combined with glucocorticoids as premedication for the prevention of adverse reactions. Reducing the dose of antivenoms or reducing the combination of antivenoms did not help to reduce the occurrence of adverse reactions. Skin testing should not be recommended due to its low sensitivity. Graphical abstract: Image 1 Highlights: We analysed the adverse reactions associated with the four types of monovalent antivenom currently used in China. The incidences of adverse reactions among the four types of monovalent antivenom showed no significant difference. The incidence of adverse reactions to the four types of monovalent antivenom was found to be low (4.9%).